Cobalt phthalocyanine / pyridine nitrogen skeleton substituted copper phthalocyanine / pitch coke activated carbon composite catalytic material as well as preparation method and application thereof

By replacing the copper phthalocyanine/pyridine nitrogen framework with copper phthalocyanine/asphalt coke activated carbon composite catalytic material, the problem of difficulty in regulating the deposition distribution of the reduction product in lithium/thionyl chloride batteries is solved, and the discharge time and voltage of the battery are improved, so as to achieve Improved performance of lithium/thionyl chloride batteries.

CN119153697AActive Publication Date: 2024-12-17ZHENGZHOU YILONG INTELLIGENT INNOVATION TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411289280.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

While the existing lithium/thionyl chloride battery positive electrode catalyst accelerates the reduction rate of SOCl2, it has a strong adsorption effect on the reduction products S and LiCl, and cannot effectively regulate the distribution of sediment, resulting in a decline in battery performance.

Method used

The purity and performance of the catalytic material of the phthalocyanine/pyridine nitrogen framework was used to replace the copper phthalocyanine/asphalt coke activated carbon composite catalytic material through a two-step solid phase method, which improved the purity and performance of the catalytic material, regulated the deposition of the SOCl2 reduction product, and enhanced the discharge of the battery. Time and discharge voltage.

Benefits of technology

The high discharge voltage and extended discharge time of lithium/thionyl chloride batteries are achieved, the overall performance of the battery is improved, and the preparation process is safe, low-cost and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005044020040000011
    Figure HDA0005044020040000011
  • Figure HDA0005044020040000012
    Figure HDA0005044020040000012
  • Figure HDA0005044020040000021
    Figure HDA0005044020040000021
Patent Text Reader

Abstract

The invention discloses a cobalt phthalocyanine / pyridine nitrogen skeleton substituted copper phthalocyanine / pitch coke activated carbon composite catalytic material and a preparation method and application thereof.The method comprises the steps that 1, pyridine-2, 3-dicarboxylic acid, urea, ammonium molybdate, copper chloride dihydrate and pitch coke activated carbon are mixed, and a mixture A is obtained; 2, carrying out heat preservation on the mixture A at 100-180 DEG C, and then carrying out heat preservation at 200-350 DEG C to obtain a product B; 3, sequentially grinding, soaking, cleaning and drying the product B to obtain pyridine nitrogen skeleton substituted copper phthalocyanine / pitch coke activated carbon; 4, mixing phthalic anhydride, urea, ammonium molybdate, cobalt chloride hexahydrate and pyridine nitrogen skeleton substituted copper phthalocyanine / pitch coke activated carbon to obtain a mixture C; 5, the mixture C is subjected to heat preservation at 100-180 DEG C and then subjected to heat preservation at 200-350 DEG C, and a product D is obtained; 6, the product D is sequentially ground, soaked, cleaned and dried, the cobalt phthalocyanine / pyridine nitrogen skeleton substituted copper phthalocyanine / pitch coke activated carbon composite catalytic material is obtained, the purity is high, the discharging time of a Li / SOCl2 battery is prolonged, and the voltage of the Li / SOCl2 battery is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a battery positive electrode catalytic material, in particular to a phthalocyanine cobalt / pyridine nitrogen skeleton substituted phthalocyanine copper / asphalt coke activated carbon composite catalytic material and a preparation method and application thereof. Background Art

[0002] Lithium / thionyl chloride batteries have a high specific capacity of 2300mAh / g, a high energy density of 710Wh / kg and a high open circuit voltage of 3.65V. The annual self-discharge rate is less than 1% and the storage life is up to 10 years. They can be used in a wide temperature range of -55℃ to 150℃. Especially when the ambient temperature is below minus 40℃, many battery systems cannot work normally, but lithium / thionyl chloride batteries can still show good performance. In addition, the discharge voltage of lithium / thionyl chloride batteries is high and stable, which can meet the requirements of precision instruments for the power supply to have a high and stable voltage platform when discharging at a high current density. Therefore, it has been widely used in aerospace, military and intelligent instruments.

[0003] Lithium / thionyl chloride batteries use metallic lithium as the negative electrode, the inorganic electrolyte LiAlCl4-SOCl2 as both the active material and the electrolyte, and carbon as the positive electrode. During the discharge process, metallic lithium reacts chemically with the electrolyte to generate products LiCl and S. When the discharge products block the carbon electrode, the battery discharge stops. During the discharge process, the lithium negative electrode and the positive carbon electrode undergo the following reactions:

[0004] Positive electrode: 2SOCl2+4e - →S+SO2+4Cl -

[0005] Negative electrode: Li-e - →Li +

[0006] Overall reaction: 4Li+2SOCl2→SO2↑+S↓+4LiCl↓

[0007] Among them, SOCl2 at the positive electrode obtains electrons to undergo a reduction reaction to generate S, SO2 and Cl - The lithium sheet at the negative electrode loses electrons to generate Li + , and migrate to the surface of the carbon positive electrode to form LiCl precipitation. With the generation of LiCl, a dense LiCl film will be generated at the carbon positive electrode. This LiCl film will hinder the transmission of electrons, the movement of ions and the diffusion of SOCl2, causing the output power and energy of the battery to drop significantly.

[0008] The performance of Li / SOCl2 batteries can be effectively improved by adding catalysts to the carbon positive electrode. However, most existing positive electrode catalysts have a strong adsorption effect on the reduction product S and LiCl while accelerating the reduction rate of SOCl2, and cannot achieve the distribution and regulation of deposits in the positive electrode and the electrode. Phthalocyanine has a two-dimensional conjugated macrocyclic structure, and the π electrons are conjugated on the entire phthalocyanine ring. The four N atoms located in the center of the structure provide favorable conditions for inserting metal atoms in the central hole. Most elements can form complexes with phthalocyanine, and it itself has good thermal and chemical stability. Studies have found that adding metal phthalocyanine complex catalytic materials to the carbon positive electrode can effectively regulate the growth of LiCl precipitation, thereby improving the performance of Li / SOCl2 batteries.

[0009] At present, the methods for preparing metal phthalocyanine complexes and their derivatives mainly include solvothermal method, microwave method and solid phase method, among which: the solvothermal method has high yield and high purity, but toxic and harmful by-products are generated during the reaction; the microwave method has a fast reaction rate, but a low yield; and the solid phase method will produce more free phthalocyanine during the preparation process, resulting in low purity of the metal phthalocyanine complexes and their derivatives. Summary of the invention

[0010] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a cobalt phthalocyanine / pyridine nitrogen skeleton substituted copper phthalocyanine / pitched coke activated carbon composite catalytic material and a preparation method and application thereof, thereby improving the purity of the composite catalytic material and thus improving the discharge time and discharge voltage of a lithium / thionyl chloride battery.

[0011] In order to achieve the above object, the present invention adopts the following technical solutions:

[0012] A method for preparing a phthalocyanine cobalt / pyridine nitrogen skeleton-substituted phthalocyanine copper / pitch coke activated carbon composite catalytic material, characterized in that it comprises the following steps:

[0013] Step 1, 0.1-2.0 g of pyridine-2,3-dicarboxylic acid, 0.15-3.0 g of urea, 0.015-0.3 g of ammonium molybdate, 0.05-1.1 g of cupric chloride dihydrate and 0.01-0.3 g of pitch coke activated carbon are mixed and ground to obtain a mixture A;

[0014] Step 2, placing mixture A in a muffle furnace, heating from room temperature to 100-180°C at a heating rate of 5-10°C / min, keeping warm for 0.5-1h, then heating to 200-350°C at a heating rate of 5-10°C / min, keeping warm for 1-4h, and naturally cooling to room temperature to obtain product B;

[0015] Step 3, grinding, soaking, washing and drying the product B in sequence to obtain pyridine nitrogen skeleton substituted copper phthalocyanine / pitch coke activated carbon;

[0016] Step 4, 0.1-2.0 g of phthalic anhydride, 0.15-3.0 g of urea, 0.015-0.3 g of ammonium molybdate, 0.08-1.5 g of cobalt chloride hexahydrate and 0.02-1.5 g of pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon are mixed and ground to obtain a mixture C;

[0017] Step 5, placing the mixture C in a muffle furnace, heating from room temperature to 100-180°C at a heating rate of 5-10°C / min, keeping the temperature for 0.5-1h, then heating to 200-350°C at a heating rate of 5-10°C / min, keeping the temperature for 1-4h, and naturally cooling to room temperature to obtain product D;

[0018] Step 6: Grind, soak, wash and dry the product D in sequence to obtain a cobalt phthalocyanine / pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon composite catalytic material.

[0019] Furthermore, the soaking in step 3 and step 6 is firstly soaking in deionized water for 8 to 24 hours, then pouring out the supernatant, and repeating 3 to 4 times.

[0020] Furthermore, the cleaning in step 3 and step 6 is performed by alternately filtering and cleaning with deionized water and anhydrous ethanol for 3 to 4 times.

[0021] Furthermore, the drying in step 3 and step 6 is performed in a vacuum drying oven at 70 to 120° C. for 10 to 28 hours.

[0022] A phthalocyanine cobalt / pyridine nitrogen skeleton substituted phthalocyanine copper / asphalt coke activated carbon composite catalytic material.

[0023] Application of cobalt phthalocyanine / pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon composite catalytic material as positive electrode catalyst for lithium / thionyl chloride batteries.

[0024] Compared with the prior art, the present invention has the following technical effects:

[0025] The present invention adopts a two-step solid phase method to prepare a phthalocyanine cobalt / pyridine nitrogen skeleton substituted phthalocyanine copper / asphalt coke activated carbon composite catalytic material. In the first step, activated carbon is used as a substrate, and a pyridine nitrogen skeleton is grown on the surface of the activated carbon to replace phthalocyanine copper; in the second step, the pyridine nitrogen skeleton substituted phthalocyanine copper / asphalt coke activated carbon synthesized in step 1 is used as a raw material to synthesize the phthalocyanine cobalt / pyridine nitrogen skeleton substituted phthalocyanine copper / asphalt coke activated carbon composite catalytic material. In the process, only simple grinding, sintering, leaching purification and drying are required. The process is not only highly safe, simple to operate, low in cost, and environmentally friendly, but also has a yield of 60%. The preparation cycle is only about 6 days. The prepared composite catalytic material has a high purity, can not only accelerate the reduction rate of SOCl2 in the discharge of a lithium / thionyl chloride battery, but also can regulate the deposition of the reduction product, thereby making the S distribution in the positive electrode and the diaphragm more uniform, and improving the discharge time and discharge voltage of the battery.

[0026] The CoPc central ion Co in the composite catalytic material prepared by the present invention 2+ The electronic configuration is 3d 7 In addition to strong coordination with the N in the phthalocyanine ligand surface, it can also strongly coordinate with the ligand (such as O in SOCl2) on the surface to form an octahedral configuration, accelerating the reduction reaction of SOCl2. 2+ For S and Cl in the product - There is also strong coordination adsorption, which will cause S and LiCl to be deposited in a concentrated manner. However, the electronic configuration of the central ion is 3d 9 The copper phthalocyanine complex of divalent copper ions is difficult to react with S, Cl - Coordination hinders the deposition of S and LiCl. Moreover, by adding activated carbon support, the reaction rate of SOCl2 and the deposition of reduction products can be regulated, so that S in the positive electrode and the separator is evenly distributed, the reaction active sites are increased, and the battery performance is further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The Raman spectra of the catalytic materials prepared in Comparative Example 1, Comparative Example 2, and Examples 1 to 3;

[0028] Figure 2 It is the infrared spectra of the catalytic materials prepared in Comparative Example 1, Comparative Example 2, and Examples 1 to 3;

[0029] FIG3( a ) is a SEM image of the catalytic material CuTAP / AC prepared in Comparative Example 1;

[0030] FIG3( b ) is a SEM image of the composite catalytic material CoPc / CuTAP / AC prepared in Example 1;

[0031] Figure 4It is a comparison diagram of discharge curves of lithium / thionyl chloride batteries containing catalytic materials prepared in Comparative Example 1, Comparative Example 2, and Examples 1 to 3, respectively, and a lithium / thionyl chloride battery without any catalytic material;

[0032] FIG5( a ) is a SEM image of a positive electrode sheet of a lithium / thionyl chloride battery containing the composite catalyst material CoPc / CuTAP / AC prepared in Example 1 after discharge and an EDS image of S in the positive electrode sheet;

[0033] FIG5( b ) is a SEM image of the positive electrode sheet of a lithium / thionyl chloride battery without any catalytic material after discharge and an EDS image of S in the positive electrode sheet;

[0034] Figure 6 This is a schematic diagram of the molecular configuration of copper phthalocyanine substituted with cobalt phthalocyanine and pyridine nitrogen skeleton. DETAILED DESCRIPTION

[0035] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0036] Example 1

[0037] Step 1, take 0.819 g of pyridine-2,3-dicarboxylic acid, 1.2 g of urea, 0.12 g of ammonium molybdate, 0.435 g of cupric chloride dihydrate and 0.1 g of pitch coke activated carbon, put them into an agate mortar, mix them evenly and grind them to obtain a mixture A;

[0038] Step 2, putting mixture A into a porcelain crucible and placing it in a muffle furnace, heating it from room temperature to 180°C at a heating rate of 10°C / min, keeping it warm for 0.5h, then heating it to 270°C at a heating rate of 10°C / min, keeping it warm for 2h, and naturally cooling it to room temperature to obtain product B;

[0039] Step 3, first scrape the product B from the wall of the porcelain crucible and grind it in an agate mortar until the particles become fine, then transfer it to a 500mL beaker, add 400mL of deionized water to the beaker, soak the collected product B for 24 hours, and after the solid particles are completely precipitated, pour out the supernatant, repeat 4 times, then use deionized water and anhydrous ethanol to filter and wash 4 times alternately, and then use a vacuum drying oven at 80°C for 24 hours to obtain pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon;

[0040] Step 4, 0.819 g of phthalic anhydride, 1.2 g of urea, 0.12 g of ammonium molybdate, 0.606 g of cobalt chloride hexahydrate and 0.14 g of pyridine nitrogen skeleton substituted copper phthalocyanine / pitched coke activated carbon were put into an agate mortar, mixed and ground evenly to obtain a mixture C;

[0041] Step 5, placing the mixture C in a porcelain crucible and placing it in a muffle furnace, heating it from room temperature to 180°C at a heating rate of 10°C / min, keeping it warm for 1h, then heating it to 270°C at a heating rate of 10°C / min, keeping it warm for 2h, and naturally cooling it to room temperature to obtain product D;

[0042] Step 6: first collect product D and grind it until the particles become fine, then transfer it to a 500 mL beaker, add 400 mL of deionized water to the beaker, soak the collected product D for 24 hours, and after the solid particles are completely precipitated, pour out the supernatant, repeat 4 times, then use deionized water and anhydrous ethanol to filter and wash alternately 4 times, and then use a vacuum drying oven at 80°C for 24 hours to obtain a cobalt phthalocyanine / pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon composite catalytic material, recorded as CoPc / CuTAP / AC 3:1.

[0043] Example 2

[0044] Step 1, take 0.819 g of pyridine-2,3-dicarboxylic acid, 1.2 g of urea, 0.12 g of ammonium molybdate, 0.435 g of cupric chloride dihydrate and 0.1 g of pitch coke activated carbon, put them into an agate mortar, mix them evenly and grind them to obtain a mixture A;

[0045] Step 2, putting mixture A into a porcelain crucible and placing it in a muffle furnace, heating it from room temperature to 180°C at a heating rate of 10°C / min, keeping it warm for 0.5h, then heating it to 270°C at a heating rate of 10°C / min, keeping it warm for 2h, and naturally cooling it to room temperature to obtain product B;

[0046] Step 3, first scrape the product B from the wall of the porcelain crucible and grind it in an agate mortar until the particles become fine, then transfer it to a 500mL beaker, add 400mL of deionized water to the beaker, soak the collected product B for 24 hours, and after the solid particles are completely precipitated, pour out the supernatant, repeat 4 times, then use deionized water and anhydrous ethanol to filter and wash 4 times alternately, and then use a vacuum drying oven at 80°C for 24 hours to obtain pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon;

[0047] Step 4, 0.819 g of phthalic anhydride, 1.2 g of urea, 0.12 g of ammonium molybdate, 0.606 g of cobalt chloride hexahydrate and 0.42 g of pyridine nitrogen skeleton substituted copper phthalocyanine / pitched coke activated carbon were put into an agate mortar, mixed and ground evenly to obtain a mixture C;

[0048] Step 5, placing the mixture C in a porcelain crucible and placing it in a muffle furnace, heating it from room temperature to 180°C at a heating rate of 10°C / min, keeping it warm for 1h, then heating it to 270°C at a heating rate of 10°C / min, keeping it warm for 2h, and naturally cooling it to room temperature to obtain product D;

[0049] Step 6: first collect product D and grind it until the particles become fine, then transfer it to a 500 mL beaker, add 400 mL of deionized water to the beaker, soak the collected product D for 24 hours, and after the solid particles are completely precipitated, pour out the supernatant, repeat 4 times, then use deionized water and anhydrous ethanol to filter and wash alternately 4 times, and then use a vacuum drying oven at 80°C for 24 hours to obtain a cobalt phthalocyanine / pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon composite catalytic material, recorded as CoPc / CuTAP / AC 1:1.

[0050] Example 3

[0051] Step 1, take 0.819 g of pyridine-2,3-dicarboxylic acid, 1.2 g of urea, 0.12 g of ammonium molybdate, 0.435 g of cupric chloride dihydrate and 0.1 g of pitch coke activated carbon, put them into an agate mortar, mix them evenly and grind them to obtain a mixture A;

[0052] Step 2, putting mixture A into a porcelain crucible and placing it in a muffle furnace, heating it from room temperature to 180°C at a heating rate of 10°C / min, keeping it warm for 0.5h, then heating it to 270°C at a heating rate of 10°C / min, keeping it warm for 2h, and naturally cooling it to room temperature to obtain product B;

[0053] Step 3, first scrape the product B from the wall of the porcelain crucible and grind it in an agate mortar until the particles become fine, then transfer it to a 500mL beaker, add 400mL of deionized water to the beaker, soak the collected product B for 24 hours, and after the solid particles are completely precipitated, pour out the supernatant, repeat 4 times, then use deionized water and anhydrous ethanol to filter and wash 4 times alternately, and then use a vacuum drying oven at 80°C for 24 hours to obtain pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon;

[0054] Step 4, 0.819 g of phthalic anhydride, 1.2 g of urea, 0.12 g of ammonium molybdate, 0.606 g of cobalt chloride hexahydrate and 1.2 g of pyridine nitrogen skeleton substituted copper phthalocyanine / pitched coke activated carbon were put into an agate mortar, mixed and ground evenly to obtain a mixture C;

[0055] Step 5, placing the mixture C in a porcelain crucible and placing it in a muffle furnace, heating it from room temperature to 180°C at a heating rate of 10°C / min, keeping it warm for 1h, then heating it to 270°C at a heating rate of 10°C / min, keeping it warm for 2h, and naturally cooling it to room temperature to obtain product D;

[0056] Step 6: first collect product D and grind it until the particles become fine, then transfer it to a 500 mL beaker, add 400 mL of deionized water to the beaker, soak the collected product D for 24 hours, and after the solid particles are completely precipitated, pour out the supernatant, repeat 4 times, then use deionized water and anhydrous ethanol to filter and wash alternately 4 times, and then use a vacuum drying oven at 80°C for 24 hours to obtain a cobalt phthalocyanine / pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon composite catalytic material, recorded as CoPc / CuTAP / AC 1:3.

[0057] Example 4

[0058] Step 1, take 0.1 g of pyridine-2,3-dicarboxylic acid, 0.15 g of urea, 0.015 g of ammonium molybdate, 0.05 g of cupric chloride dihydrate and 0.01 g of pitch coke activated carbon, put them into an agate mortar, mix them evenly and grind them to obtain a mixture A;

[0059] Step 2, placing mixture A in a porcelain crucible and placing it in a muffle furnace, heating from room temperature to 100°C at a heating rate of 5°C / min, keeping warm for 1h, then heating to 200°C at a heating rate of 5°C / min, keeping warm for 4h, and naturally cooling to room temperature to obtain product B;

[0060] Step 3, first scrape the product B from the wall of the porcelain crucible and grind it in an agate mortar until the particles become fine, then transfer it to a 500mL beaker, add 400mL of deionized water to the beaker, soak the collected product B for 8 hours, and after the solid particles are completely precipitated, pour out the supernatant, repeat 3 times, then use deionized water and anhydrous ethanol to filter and wash 3 times alternately, and then use a vacuum drying oven at 70°C for 28 hours to obtain pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon;

[0061] Step 4, 0.1 g of phthalic anhydride, 0.15 g of urea, 0.015 g of ammonium molybdate, 0.08 g of cobalt chloride hexahydrate and 0.02 g of pyridine nitrogen skeleton substituted copper phthalocyanine / pitched coke activated carbon were put into an agate mortar, mixed and ground evenly to obtain a mixture C;

[0062] Step 5, placing the mixture C in a porcelain crucible and placing it in a muffle furnace, heating it from room temperature to 100°C at a heating rate of 5°C / min, keeping it warm for 0.5h, then heating it to 200°C at a heating rate of 5°C / min, keeping it warm for 4h, and naturally cooling it to room temperature to obtain product D;

[0063] Step 6: first collect product D and grind it until the particles become fine, then transfer it to a 500 mL beaker, add 400 mL of deionized water to the beaker, soak the collected product D for 8 hours, and after the solid particles are completely precipitated, pour out the supernatant, repeat 3 times, then use deionized water and anhydrous ethanol to filter and wash 3 times alternately, and then use a vacuum drying oven at 70°C for 28 hours to obtain a cobalt phthalocyanine / pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon composite catalytic material, recorded as CoPc / CuTAP / AC 1:4

[0064] Example 5

[0065] Step 1, take 2.0 g of pyridine-2,3-dicarboxylic acid, 3.0 g of urea, 0.3 g of ammonium molybdate, 1.1 g of cupric chloride dihydrate and 0.3 g of pitch coke activated carbon, put them into an agate mortar, mix them evenly and grind them to obtain a mixture A;

[0066] Step 2, putting mixture A into a porcelain crucible and placing it in a muffle furnace, heating from room temperature to 140°C at a heating rate of 7°C / min, keeping warm for 1h, then heating to 350°C at a heating rate of 7°C / min, keeping warm for 1h, and naturally cooling to room temperature to obtain product B;

[0067] Step 3, first scrape the product B from the wall of the porcelain crucible and grind it in an agate mortar until the particles become fine, then transfer it to a 500mL beaker, add 400mL of deionized water to the beaker, soak the collected product B for 20 hours, and after the solid particles are completely precipitated, pour out the supernatant, repeat 3 times, then use deionized water and anhydrous ethanol to filter and wash 4 times alternately, and then use a vacuum drying oven at 120°C for 10 hours to obtain pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon;

[0068] Step 4, 2.0 g of phthalic anhydride, 3.0 g of urea, 0.3 g of ammonium molybdate, 1.5 g of cobalt chloride hexahydrate and 1.5 g of pyridine nitrogen skeleton substituted copper phthalocyanine / pitched coke activated carbon were put into an agate mortar, mixed and ground evenly to obtain a mixture C;

[0069] Step 5, the mixture C was placed in a porcelain crucible and placed in a muffle furnace, and the temperature was increased from room temperature to 140°C at a heating rate of 7°C / min, and the temperature was kept for 0.5h, and then the temperature was increased to 350°C at a heating rate of 7°C / min, and the temperature was kept for 1h, and the mixture was naturally cooled to room temperature to obtain product D;

[0070] Step 6: first collect product D and grind it until the particles become fine, then transfer it to a 500 mL beaker, add 400 mL of deionized water to the beaker, soak the collected product D for 20 hours, and after the solid particles are completely precipitated, pour out the supernatant, repeat 3 times, then use deionized water and anhydrous ethanol to filter and wash alternately 4 times, and then use a vacuum drying oven at 120°C for 10 hours to obtain a cobalt phthalocyanine / pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon composite catalytic material, recorded as CoPc / CuTAP / AC2:3.

[0071] Example 6

[0072] Step 1, take 1.05 g of pyridine-2,3-dicarboxylic acid, 1.6 g of urea, 0.16 g of ammonium molybdate, 0.58 g of cupric chloride dihydrate and 0.16 g of pitch coke activated carbon, put them into an agate mortar, mix them evenly and grind them to obtain a mixture A;

[0073] Step 2, placing mixture A in a porcelain crucible and placing it in a muffle furnace, heating from room temperature to 160°C at a heating rate of 8°C / min, keeping warm for 1h, then heating to 300°C at a heating rate of 8°C / min, keeping warm for 3h, and naturally cooling to room temperature to obtain product B;

[0074] Step 3, first scrape the product B from the wall of the porcelain crucible and grind it in an agate mortar until the particles become fine, then transfer it to a 500mL beaker, add 400mL of deionized water to the beaker, soak the collected product B for 16 hours, and after the solid particles are completely precipitated, pour out the supernatant, repeat 4 times, then use deionized water and anhydrous ethanol to filter and wash 3 times alternately, and then use a vacuum drying oven at 100°C for 18 hours to obtain pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon;

[0075] Step 4, 1.05 g of phthalic anhydride, 1.6 g of urea, 0.16 g of ammonium molybdate, 0.79 g of cobalt chloride hexahydrate and 0.8 g of pyridine nitrogen skeleton substituted copper phthalocyanine / pitched coke activated carbon were put into an agate mortar, mixed and ground evenly to obtain a mixture C;

[0076] Step 5, the mixture C was placed in a porcelain crucible and placed in a muffle furnace, and the temperature was increased from room temperature to 160°C at a heating rate of 8°C / min, and kept warm for 0.5h, and then the temperature was increased to 300°C at a heating rate of 8°C / min, and kept warm for 3h, and naturally cooled to room temperature to obtain product D;

[0077] Step 6. First collect product D and grind it until the particles become fine, then transfer it to a 500mL beaker, add 400mL of deionized water to the beaker, soak the collected product D for 16 hours, and after the solid particles are completely precipitated, pour out the supernatant, repeat 4 times, then use deionized water and anhydrous ethanol to filter and wash alternately 3 times, and then use a vacuum drying oven at 100°C for 18 hours to obtain a cobalt phthalocyanine / pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon composite catalytic material, recorded as CoPc / CuTAP / AC2:3.

[0078] Comparative Example 1

[0079] Step 1, take 0.819 g of pyridine-2,3-dicarboxylic acid, 1.2 g of urea, 0.12 g of ammonium molybdate, 0.435 g of cupric chloride dihydrate and 0.1 g of pitch coke activated carbon, put them into an agate mortar, mix and grind them evenly to obtain a mixture A;

[0080] Step 2, putting mixture A into a porcelain crucible and placing it in a muffle furnace, heating it from room temperature to 180°C at a heating rate of 10°C / min, keeping it warm for 1h, then heating it to 270°C at a heating rate of 10°C / min, keeping it warm for 2h, and naturally cooling it to room temperature to obtain product B;

[0081] Step 3: scrape product B from the wall of the porcelain crucible and grind it in an agate mortar until the particles become fine, then transfer it to a 500mL beaker, add 400mL of deionized water to the beaker, soak the collected product B for 24 hours, and after the solid particles are completely precipitated, pour out the supernatant, repeat the operation 4 times, then use deionized water and anhydrous ethanol to filter and wash 4 times alternately, then use a vacuum drying oven at 80°C, dry for 24 hours, grind, and obtain pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon, recorded as CuTAP / AC.

[0082] Comparative Example 2

[0083] Step 1, take 0.819 g of phthalic anhydride, 1.2 g of urea, 0.12 g of ammonium molybdate, and 0.607 g of cobalt chloride hexahydrate, put them into an agate mortar, mix and grind them evenly to obtain a mixture A;

[0084] Step 2, putting mixture A into a porcelain crucible and placing it in a muffle furnace, heating it from room temperature to 180°C at a heating rate of 10°C / min, keeping it warm for 1h, then heating it to 270°C at a heating rate of 10°C / min, keeping it warm for 2h, and naturally cooling it to room temperature to obtain product B;

[0085] Step 3: scrape product B from the wall of the porcelain crucible and grind it in an agate mortar until the particles become fine, then transfer it to a 500mL beaker, add 400mL of deionized water to the beaker, soak the collected product B for 24 hours, and after the solid particles are completely precipitated, pour out the supernatant, repeat the operation 4 times, then use deionized water and anhydrous ethanol to filter and wash 4 times alternately, and then use a vacuum drying oven at 80°C for 24 hours, grind, and obtain cobalt phthalocyanine catalytic material, recorded as CoPc.

[0086] from Figure 1 It can be seen that the CoPc / CuTAP / AC prepared in Examples 1 to 3 have a wavelength of 729, 1086, 1121, 1290, 1329, 1420, 1520, 1593 and 1639 cm -1 The presence of these peaks corresponds to the vibration of the CoPc and CuTAP molecular skeletons, especially 729 cm -1 and 1086cm -1 The peaks at 1121cm -1 The peak position of 1420cm -1 The absorption peak at 1425 cm-1 can be explained as the absorption peak at 1425 cm-1 during the interaction between CoPc and CuTAP / AC. -1 and 1394cm -1 The peaks of merged, indicating that Examples 1 to 3 successfully synthesized the cobalt phthalocyanine / pyridine nitrogen skeleton substituted copper phthalocyanine / pitch coke activated carbon composite catalytic material CoPc / CuTAP / AC.

[0087] from Figure 2 It can be seen that CoPc is at 598, 683, 752, and 1142 cm -1 The peaks at 832, 937, 1142, 1340, and 1537 cm -1 The peaks appearing at all indicate the interaction between CoPc and CuTAP / AC, further illustrating that Examples 1 to 3 successfully synthesized the cobalt phthalocyanine / pyridine nitrogen skeleton substituted copper phthalocyanine / pitched coke activated carbon composite catalytic material CoPc / CuTAP / AC.

[0088] As can be seen from Figure 3(a), the particle size of the CuTAP block in the catalytic material CuTAP / AC prepared in Comparative Example 1 is about 4um; as can be seen from Figure 3(b), in the composite catalytic material CoPc / CuTAP / AC prepared in Example 1, the particle size of the CuTAP block is about 2um, and the composite CoPc thereon is refined into small particles with a particle size distribution in the range of tens of nanometers, which increases the specific surface area of ​​CoPc and CuTAP, fully exposes the active sites, thereby improving the reduction rate of thionyl chloride, and can effectively regulate the distribution of reduction products.

[0089] In order to verify the influence of the content of CoPc and CuTAP / AC on the discharge time and discharge voltage of the battery, the same process parameters were used in Examples 1 to 3 to prepare composite catalytic materials CoPc / CoTAP / CuPc3:1, CoPc / CoTAP / CuPc1:1 and CoPc / CoTAP / CuPc1:3, respectively. At the same time, Comparative Examples 1 and 2 prepared catalytic materials CuTAP / AC and CoPc, respectively. Then, the catalytic materials prepared in Comparative Example 1, Comparative Example 2 and Examples 1 to 3 were added to the positive electrode of the lithium / thionyl chloride battery, and the lithium / thionyl chloride battery was assembled for performance testing. At the same time, the lithium / thionyl chloride battery without the addition of the catalytic material was used as the control group, marked as bare. The results are as follows: Figure 4 As shown, without adding a catalyst, the initial discharge voltage of the battery is 2.8V, and the discharge process lasts for 18 minutes. After adding the catalyst CoPc prepared in Comparative Example 2, the discharge voltage of the battery is increased to 3.08V, but the discharge time is not significantly increased, indicating that CoPc can increase the discharge voltage of the battery; after adding the catalyst CuTAP / AC prepared in Comparative Example 1, the discharge voltage of the battery does not change significantly, but the discharge time is extended to 28 minutes, indicating that the catalyst CuTAP / AC can increase the discharge time of the battery; for lithium / thionyl chloride batteries to which the composite catalytic materials CoPc / CoTAP / CuPc1:3, CoPc / CoTAP / CuPc1:1 and CoPc / CoTAP / CuPc3:1 are added, respectively, the discharge voltage gradually increases with the increase of the CoPc ratio, and at the same time, the discharge time also increases, especially after adding CoPc / CoTAP / CuPc3:1 prepared in Example 1, that is, when the ratio of CoPc to CuTAP / AC is 3:1, the discharge voltage and discharge time are both optimal.

[0090] The deposition distribution of S was tested by EDS on the positive electrode sheet added with CoPc / CoTAP / CuPc3:1 prepared in Example 1 after discharge. The result is shown in FIG5( a). It can be seen that the reduction product S produced by the decomposition of thionyl chloride SOCl2 is very uniformly distributed on the surface of the carbon positive electrode, indicating that the catalyst CoPc / CoTAP / CuPc effectively regulates the formation and deposition process of the reduction product, avoids local excessive accumulation, and thus promotes the uniform utilization of the electrochemically active substances on the entire electrode surface.

[0091] The deposition distribution of S was tested by EDS on the positive electrode sheet without adding any catalyst after discharge. The result is shown in Figure 5(b). It can be seen that without adding any catalyst, the deposition of S on the carbon positive electrode is very uneven, that is, dense deposition of sulfur is observed in some areas, while sulfur is almost invisible in other areas. This phenomenon leads to unstable battery performance and low efficiency.

[0092] from Figure 6 It can be seen that the central metal ion Co 2+ It forms a relatively stable octahedral configuration with macrocyclic phthalocyanine. In the process of reducing SOCl2, the interaction between CoPc and SOCl2 is mainly the coordination bond between the central metal ion and the O atom of SOCl2 and various van der Waals forces. Because of its strong adsorption, the product LiCl generated during battery discharge is densely stacked inside the electrode. However, for CuTAP, due to Cu 2+ The outer electrons of Cu are 9, and the splitting energy of its orbit is relatively large, so 2+ The d orbital filling will become t 2g 6 e g 3 , where e g The orbital distribution is (d z2 ) 1 (d x2-y2 ) 2 , which increases the bond length shortening energy level on the x and y plane axes, and decreases the bond length elongation energy level on the z axis, eliminating the e g (d z2, d x2-y2 ) degeneracy, forming four coplanar short bonds and two long bonds perpendicular to the plane, thus producing Jan-Taylor distortion, making it form an elongated octahedral configuration. In addition, the coordination number of CuTAP is 4. Due to Jan-Taylor distortion, the planar geometry of CuTAP is distorted into a square. In the process of reducing SOCl2, the Cu 2+It is difficult to form coordination bonds with the O atoms of SOCl2, so the binding between CuTAP and SOCl2 can only be maintained by partial van der Waals force, and the binding between the two is weak, so the reaction products LiCl and S can be efficiently transferred.

Claims

1. A method for preparing a phthalocyanine cobalt / pyridine nitrogen skeleton-substituted phthalocyanine copper / pitch coke activated carbon composite catalytic material, characterized in that: The steps include: Step 1, 0.1-2.0 g of pyridine-2,3-dicarboxylic acid, 0.15-3.0 g of urea, 0.015-0.3 g of ammonium molybdate, 0.05-1.1 g of cupric chloride dihydrate and 0.01-0.3 g of pitch coke activated carbon are mixed and ground to obtain a mixture A; Step 2, placing mixture A in a muffle furnace, heating from room temperature to 100-180°C at a heating rate of 5-10°C / min, keeping warm for 0.5-1h, then heating to 200-350°C at a heating rate of 5-10°C / min, keeping warm for 1-4h, and naturally cooling to room temperature to obtain product B; Step 3, grinding, soaking, washing and drying the product B in sequence to obtain pyridine nitrogen skeleton substituted copper phthalocyanine / pitch coke activated carbon; Step 4, 0.1-2.0 g of phthalic anhydride, 0.15-3.0 g of urea, 0.015-0.3 g of ammonium molybdate, 0.08-1.5 g of cobalt chloride hexahydrate and 0.02-1.5 g of pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon are mixed and ground to obtain a mixture C; Step 5, placing the mixture C in a muffle furnace, heating from room temperature to 100-180°C at a heating rate of 5-10°C / min, keeping the temperature for 0.5-1h, then heating to 200-350°C at a heating rate of 5-10°C / min, keeping the temperature for 1-4h, and naturally cooling to room temperature to obtain product D; Step 6: Grind, soak, wash and dry the product D in sequence to obtain a cobalt phthalocyanine / pyridine nitrogen skeleton substituted copper phthalocyanine / asphalt coke activated carbon composite catalytic material.

2. The method for preparing the cobalt phthalocyanine / pyridine nitrogen skeleton-substituted copper phthalocyanine / pitch coke activated carbon composite catalytic material according to claim 1, characterized in that: The soaking in step 3 and step 6 is to first soak in deionized water for 8 to 24 hours, then pour out the supernatant, and repeat 3 to 4 times.

3. The method for preparing the cobalt phthalocyanine / pyridine nitrogen skeleton-substituted copper phthalocyanine / pitch coke activated carbon composite catalytic material according to claim 1, characterized in that: The cleaning in step 3 and step 6 is performed by alternately filtering and cleaning with deionized water and anhydrous ethanol for 3 to 4 times.

4. The method for preparing the cobalt phthalocyanine / pyridine nitrogen skeleton-substituted copper phthalocyanine / pitch coke activated carbon composite catalytic material according to claim 1, characterized in that: The drying in step 3 and step 6 is performed in a vacuum drying oven at 70 to 120° C. for 10 to 28 hours.

5. A cobalt phthalocyanine / pyridine nitrogen skeleton-substituted copper phthalocyanine / pitch coke activated carbon composite catalytic material prepared by the method according to any one of claims 1 to 4.

6. Use of the cobalt phthalocyanine / pyridine nitrogen skeleton-substituted copper phthalocyanine / pitch coke activated carbon composite catalytic material according to claim 5 as a positive electrode catalyst for lithium / thionyl chloride batteries.

Citation Information

Patent Citations

  • Nitrogen modified carbon loaded copper catalyst and application thereof in field of battery anode material

    CN109378473A

  • Nickel tetrapyridylporphyrin, copper tetrapyridylporphyrin and activated carbon Li / SOCl2 battery positive electrode catalytic material, and preparation method thereof

    CN112968162A

  • Transition metal phthalocyanine coated phthalocyanine blue / pitch coke activated carbon composite material lithium-thionyl chloride battery positive electrode catalyst and preparation method thereof

    CN114068965A

  • Lithium / thionyl chloride battery positive electrode catalytic material CoPc / CuPc and preparation method thereof

    CN114100687A

  • Metal phthalocyanine complex / carbon composite material modified lithium-sulfur battery diaphragm and preparation method thereof

    CN116526067A

Cited By

  • Electrode material containing phthalic anhydride-based porous carbon and preparation method thereof

    CN120511305A